(untitled) (Journal of Human Sciences, 2026)
This study aims to compare and analyse the discourse used in two advertisements with reference to interpersonal features such as; commands, questions, interactive pronouns, modalisation, and attitudinal evaluation. This is a descriptive qualitative method. The first advertisement, referred to this paper as IDA2, promotes private health insurance, while the second, referred to as IDA3, advertises a private clinic specialising in cosmetic surgery. The collected data were the words, phrases, clauses, and sentences that are used in ads. The findings reveal that both advertisements share several linguistic similarities, yet they also exhibit notable differences. Furthermore, this paper compares how these interpersonal features are employed to influence and persuade readers, encouraging engagement with the advertised products. This paper concludes that such interpersonal features play a crucial role in shaping audience perception and enhancing the persuasive impact of adverting discourse. This paper recommends further research to be conducted to explore relevant types of discourse analysis related to this study with different areas.